Stiffness and Adhesivity Control Aortic Valve Interstitial Cell Behavior within Hyaluronic Acid Based Hydrogels - Duan, Bin (2013)
Bioactive and biodegradable hydrogels that mimic the extracellular matrix and regulate valve interstitial cells (VIC) behavior are of great interest as three dimensional (3D) model systems for understanding mechanisms of valvular heart disease pathogenesis in vitro and the basis for regenerative templates for tissue engineering. However, the role of stiffness and adhesivity of hydrogels in VIC behavior remains poorly understood. This study reports synthesis of oxidized and methacrylated hyaluronic acid (Me-HA and MOHA) and subsequent development of hybrid hydrogels based on modified HA and methacrylated gelatin (Me-Gel) for VIC encapsulation. The mechanical stiffness and swelling ratio of the hydrogels were tunable with molecular weight of HA and concentration/composition of precursor solution. The encapsulated VIC in pure HA hydrogels with lower mechanical stiffness showed more spreading morphology comparing to stiffer counterparts and dramatically upregulated alpha smooth muscle actin expression indicating more activated myofibroblast properties. The addition of Me-Gel in Me-HA facilitated cell spreading, proliferation and VIC migration from encapsulated spheroids and better maintained VIC fibroblastic phenotype. The VIC phenotype transition during migration from encapsulated spheroids in both Me-HA and Me-HA/Me-Gel hydrogel matrix was also observed. These findings are important for the rational design of hydrogels for controlling VIC morphology, and for regulating VIC phenotype and function. The Me-HA/Me-Gel hybrid hydrogels accommodated with VIC are promising as valve tissue engineering scaffolds and 3D model for understanding valvular pathobiology.